ISOLATION AND CHARACTERIZATION OF PYOCIN S2-PRODUCING LOCAL STRAINS OF Pseudomonas aeruginosa - Sika, Gladys Aribi; Wayah, Samson Baranzan; Waziri, Peter Maitalata (FUDMA JOURNAL OF SCIENCES, 2025)
Antibiotic resistance is responsible for 1.27 million deaths globally. Pyocin, from Pseudomonas aeruginosa is a promising candidate against antibiotic-resistant infections. This study aims at isolating pyocin S2-producing local strains of Pseudomonas aeruginosa and investigating the antimicrobial activity of pyocin S2 against Staphylococcus aureus, Staphylococcus sp., Escherichia coli, Salmonella sp., Streptococcus pneumoniae, and Vibrio cholerae. Pseudomonas aeruginosa was isolated from environmental and clinical samples by inoculation on cetrimide agar plates and incubating at 370C for 24 hours. To detect the presence of pyocin S2 gene in the isolates: DNA extraction, polymerase chain reaction (PCR) using primers specific to pyocin S2 gene, and agarose gel electrophoresis was conducted. Using agar well diffusion assay, the antimicrobial activity of pyocin S2-containing Pseudomonas aeruginosa against the aforementioned target pathogens was evaluated. Out of 20 Pseudomonas aeruginosa isolates subjected to PCR, 11 contained pyocin S2 gene. Pyocin S2 from Pseudomonas aeruginosa A1, B2, CL2, CL8 and C11 produced zone of inhibition (ZOI) when tested against Escherichia coli (ZOI = 23.5mm, 17.5mm, 26.0mm, 21.5mm, 29.0mm respectively). However, pyocin S2 from Pseudomonas aeruginosa B3, B10, CL3, B19, CL9 and CL6 did not inhibit Escherichia coli but suppressed the growth of Staphylococcus sp. (ZOI = 21.0mm, 18.5mm, 28.5mm, 23.7mm, 24.5mm and 23.5mm respectively). Also, Pyocin S2 from Pseudomonas aeruginosa C11 suppressed the growth of Vibrio cholerae (ZOI = 30.7mm), but not the other strains. In conclusion, pyocin S2 from indigenous strains of Pseudomonas aeruginosa inhibited the target pathogens. These findings will foster further evaluation of pyocin S2’s antimicrobial potential.